Cinética de degradación de carotenos y vitamina c, en un suplemento vitamínico, de bajo poder calórico - Herrera Soria, Pablo Gilberto (2023)
In recent decades, cancer and other serious illnesses have been present in people of all ages, being one of the causes of greatest mortality on the planet, therefore, it is necessary to propose new products for the food market; This research proposed a vitamin gelatin supplement based on astaxanthin carotene and vitamin C, powerful antioxidants; fructose and sucralose as low caloric sweeteners. Variables were established for an AxB experimental design with two repetitions, in order to determine the best treatments for their sensory attributes, taking into consideration, the application of two kinetic models: zero order and first order, to determine the correlation coefficient, the constant of degradation, and the microbiological characteristics that allow an innocuous food product to have good antioxidant characteristics. Treatments were stored at 8°C throughout the study.